Automated detection of Malignant Lesions in the ovary using deep learning models and XAI - Ifty, Md. Hasin Sarwar; Nirjan, Nisharga; Diganta, M.A.; Islam, Labib; Ornate, Reeyad Ahmed (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.